2006
DOI: 10.1021/es051932b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Quality of Structured Environmental Management Decisions

Abstract: Structured decision making (SDM) approaches have been advocated as a means of improving the quality of environmental and related risk management decisions based largely on the self-reported behavior of decision makers. The goal of the research presented here was to test this basis for decision quality by comparing the selfreported assessments of individual decision makers with their actual choice behavior across a set of three related environmental contexts. It was hypothesized that a modified structured decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 35 publications
(62 reference statements)
1
35
0
Order By: Relevance
“…Most expert discussions of decision quality focus on the extent to which a given decision meets certain process-oriented criteria (National Research Council 2005;Wilson and Arvai 2006). However, the results reported here suggest that outside observers (namely members of 'the public') do not use process-based criteria to evaluate decision quality and rely on the suitability of outcomes instead.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Most expert discussions of decision quality focus on the extent to which a given decision meets certain process-oriented criteria (National Research Council 2005;Wilson and Arvai 2006). However, the results reported here suggest that outside observers (namely members of 'the public') do not use process-based criteria to evaluate decision quality and rely on the suitability of outcomes instead.…”
Section: Discussionmentioning
confidence: 72%
“…The HQ process was described in terms of participatory and structured decisionmaking (SDM) akin to the process outlined by Keeney (1992) and others (von Winterfeldt and Edwards 1986;Hammond, Keeney, and Raiffa 1999;Gregory 2000;Gregory, Arvai, and McDaniels 2001;National Research Council 2005;Wilson and Arvai 2006), and later field tested in a variety of contexts (McDaniels, Gregory, and Fields 1999;Gregory and Wellman 2001;Arvai and Gregory 2003;Wilson and McDaniels 2007). Briefly, SDM processes are designed based on insights from behavioral decision research (Mellers, Schwartz, and Cooke 1998;Slovic and Lichtenstein 2006) and multiattribute utility theory (Keeney and Raiffa 1993), and are defined by engaging relevant stakeholders in the following tasks: (1) defining the decision to be made; (2) identifying stakeholders' objectives in context of the decision; (3) creating a set of alternatives that are sensitive to stakeholders' objectives to address the problem; (4) identifying consequences across objectives that are associated with each alternative; and (5) addressing the important tradeoffs that choosing one alternative over another entails.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…). Instead, methods to measure outcomes depend on site‐specific conditions and individual project parameters (Wilson and Arvai ). The novel ecosystem concept expands the potential suite of management objectives for modified ecosystems by removing limitations of conservative conservation strategies and increasing flexibility to work with the extant system (Hobbs et al .…”
Section: Novel Ecosystems As Legitimate Management Targetsmentioning
confidence: 99%
“…Others have noted the difference between individuals' initial -value-judgments‖ and reasoned values-based decisions. For example, Wilson and Arvai (2006) found that participants in an experiment were unable to stay focused on stated conservation values (objectives) that were intended for a formal decision-making process, and ultimately, participants made decisions that reflected their initial affective impressions that aligned with informal mental processes (Wilson, 2008). In contrast, formal decision-making is rooted in internal consistency between a suite of values and a reasoned analysis of tradeoffs instead of being rooted in affective impressions.…”
Section: Objectivesmentioning
confidence: 99%